The AIATSIS Return of Cultural Heritage Project: Understanding Aboriginal and Torres Strait Islander Cultural Heritage Material Held Overseas and the Initial Challenges to Repatriating Material to Custodians. (5th October 2021) - Johnston, Iain G.; Meara, Tamarind; Ley, Lyndall; Simpson, Christopher; Lyons, Jason; Rutherford, Rose; Quadri, Diana
Abstract: This paper explores the first research phase of the AIATSIS Return of Cultural Heritage Project (2018–2020); where AIATSIS scoped, researched and repatriated significant cultural heritage material from overseas collecting institutions to Aboriginal and Torres Strait Islander communities in Australia. In the initial research phase, the authors undertook a survey of international collecting institutions to scope their holdings of Aboriginal and Torres Strait Islander material culture and their willingness to repatriate significant objects to Aboriginal and Torres Strait Islander communities. The results of this survey demonstrate a readiness of institutions to share collection records with AIATSIS and a desire by those institutions to have relationships with the First Nations represented in their collections. The authors also found a willingness by a considerable portion of international collecting institutions to consider the repatriation of cultural heritage material to Aboriginal and Torres Strait Islander communities. The final part of the paper evaluates the effectiveness of these collection records and associated public repatriation and deaccession polices to submit a repatriation request for the return of significant Aboriginal or Torres Strait Islander cultural heritage material to communities in Australia.